Assessing How Orphan Girls are Handled in Kaliro District : a case study of bukumankoola village - Basalirwa, Norah (Mukono : Uganda Christian University, 2009)
Discriptive Cataloguing Uganda Christian University, BCDCM
Includes reference and appendix
Keywords: Orphan Girls